Pengaruh Pembelajaran Secara Daring pada Masa Pandemi Covid-19 terhadap Minat Belajar pada Mahasiswa PGPAUD - Della, Ellyta Iman; Aljamaliah, Syifa (JURNAL PENDIDIKAN, 2021)
Abstrack: With the Covid-19 pandemic, the learning process in lectures is carried out with an online remote system (brave). In this study, the aim of this research is to see how bold learning affects students' interest in learning during the Covid-19 pandemic. The method used in this research is qualitative method. The technique used is interviews by spreading open questionnaires and also making observations. The subjects of this study were students majoring in Paud Teacher Education, Universitas Pendidikan Indonesia. The sampling technique used purposive sampling technique. From the research conducted, it was found that the students' interest in learning from the Department of Early Childhood Teacher Education at the University of Pendidikan Indonesia was still high even though there were some students whose interest in learning had decreased. The conclusion of this study is that learning has an effect on students, whether there is an increase or decrease in the learning interest of students in the Department of Teacher Education at the Indonesian Education University.Key Words: Online learning, interest in learning, pandemic, covid-19